Transversely isotropic mechanical properties of water-bearing shale: An experimental investigation. Issue 2 (October 2021) - Zheng, Zhao-Qiang; Xiao, Ming-Li; Zhuo, Li; Xie, Hong-Qiang; Liu, Huai-Zhong
Abstract: This study investigated the transversely isotropic properties of water-bearing shale by performing laboratory experiments on shale specimens with different bedding angles of 0°, 45°, and 90° under different saturation conditions. X-ray diffraction, P-wave velocity, and water absorption tests reveal that the studied shale features low porosity and brittleness. During uniaxial compression tests, transversely isotropic and axial apparent moduli degrade linearly with increasing saturation degree, but the former shows more significant changes than the latter. The Poisson's ratio in the direction perpendicular to the bedding plane decreases with increasing saturation degree, whereas that in the parallel direction shows the opposite behavior. Weak transverse isotropy is observed on the uniaxial compression strength of air-dried specimens. As the saturation degree is increased, strengths corresponding to different bedding angles degrade linearly, and the transverse isotropic strength is weakened. Despite the significant degradation of strength, the brittle failure patterns and the fraction of dissipated energy density of the specimens do not change with saturation degree.